The Survival of Salmonella Senftenberg, Escherichia coli O157:H7, Listeria monocytogenes, Enterococcus faecalis and Clostridium sporogenes in Sandy and Clay Loam Textured Soils When Applied in Bovine Slurry or Unpasteurised Digestate and the Run-Off Rate for a Test Bacterium, Listeria innocua, When Applied to Grass in Slurry and Digestate - Russell, Lauren; Whyte, Paul; Zintl, Annetta; Gordon, Stephen V.; Markey, Bryan; de Waal, Theo; Nolan, Stephen; O'Flaherty, Vincent; Abram, Florence; Richards, Karl; Fenton, Owen; Bolton, Declan (Frontiers in Sustainable Food Systems, 2022)
This study investigated the survival of Salmonella Senftenberg, Escherichia coli O157:H7, Listeria monocytogenes, Enterococcus faecalis and Clostridium sporogenes in sandy and clay loam textured soils when applied in bovine slurry or unpasteurised digestate, using laboratory based inoculation studies. The run-off rate for a test bacterium, Listeria innocua, when applied to grass in slurry and digestate, was also examined using field studies. Bovine slurry and digestate were inoculated with the target bacteria to a final concentration of 106 log10 cfu/g or spores/g, thoroughly mixed into soil samples and incubated at 4°C or 14°C. Samples were removed periodically and the surviving cells enumerated using AOAC or equivalent methods. The loss of viability/culturability phase followed first order kinetics and T90 values ranged from 11.9 to 166.7 d at 4°C and from 6.0 to 156 d at 14°C. With the exception of E. coli O157:H7 and E. faecalis in sandy loam textured soil at 14°C (T90 values were significantly (P < 0.05) higher in slurry) the type of soil texture or application material (slurry or digestate) did not affect survival rates. In the field study, 12 grass covered micro-plots were prepared. L. innocua was applied in digestate and bovine slurry and rainfall was simulated at a target rate of ~11 mm per plot per h−1. Rainfall simulation (30 min) took place after 24, 48 h, 14 d and 30 d. Run-off samples were tested for the L. innocua strain using Brilliance Listeria agar supplemented with streptomycin sulphate (1,000 μg/ml) at 37°C for 48 h, as were soil samples after 30, 58, 86 and 112 d. Significantly (P < 0.05) lower counts were obtained in the run-off from digestate after 1, 2 and 30 d as compared to slurry. It was concluded that the type of organic fertiliser does not affect the bacterial survival rates in sandy and clay soils, with the exception of E. coli O157:H7 and E. faecalis in sandy loam textured soil at 14°C. Furthermore, bacteria may be retained better in the soil-digestate matrices during rainfall although additional research is required to further validate and provide the scientific basis for this observation.